The red onion (Allium ascatonicum L.) marketing strategy is based in the Rejoso District, Mojorembaun Village, and Nganjuk Regency. - Susilo, Andi Dwi; Takarijanto, Sugeng; Bawono, Muhammad (Politeknik Negeri Jember, 2025)
Shallots (Allium ascalonicum L) are annual plants and constitute a high-value horticultural commodity. As the harvest season nears, farmers encounter the issue of declining prices resulting from the synchronization of harvest schedules across various locations. In light of this predicament, it is essential to develop a marketing strategy to ensure that farmers maintain adequate income. This research seeks to elucidate external elements (opportunities and threats) and internal factors (strengths and weaknesses) to identify suitable marketing strategy alternatives and to prioritize marketing strategies. The employed data processing and analysis methodology is SWOT analysis, encompassing Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and the Internal-External (IE) matrix, then enhanced through the SWOT Matrix, along with the identification of priority strategies via Quantitative Strategic Planning Matrix (QSPM) analysis. The QSPM study indicates that the primary marketing strategy for red onions in Mojorembun Village is to set cultivation objectives by instituting standard operating procedures (SOP) for red onion production to enhance competitiveness, reflected by a TAS score of 7.409.